2014
DOI: 10.1155/2014/725813
|View full text |Cite
|
Sign up to set email alerts
|

100 Gy60Coγ-Ray Induced Novel Mutations in Tetraploid Wheat

Abstract: 10 accessions of tetraploid wheat were radiated with 100 Gy 60Co γ-ray. The germination energy, germination rate, special characters (secondary tillering, stalk with wax powder, and dwarf), meiotic process, and high-molecular-weight glutenin subunits (HMW-GSs) were observed. Different species has different radiation sensibility. With 1 seed germinated (5%), T. dicoccum (PI434999) is the most sensitive to this dose of radiation. With a seed germination rate of 35% and 40%, this dose also affected T. polonicum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The effects of irradiationon the frequency of chromosomal aberrations, rate of germination, and changes in morphological and physiological traits have been previously documented [ 16 , 17 , 18 , 19 ]. In agreement with the findings of previous studies on wheat- Aegilops biuncialis amphiploids [ 19 , 20 ], those of the present study suggested the presence of translocations, fragments, and dicentrics in all three dosage groups (100, 200, and 300 Gy).Furthermore, the frequency of aberrances increased with an increase in the irradiation dose in the M 0 generation of the irradiated line WD14.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of irradiationon the frequency of chromosomal aberrations, rate of germination, and changes in morphological and physiological traits have been previously documented [ 16 , 17 , 18 , 19 ]. In agreement with the findings of previous studies on wheat- Aegilops biuncialis amphiploids [ 19 , 20 ], those of the present study suggested the presence of translocations, fragments, and dicentrics in all three dosage groups (100, 200, and 300 Gy).Furthermore, the frequency of aberrances increased with an increase in the irradiation dose in the M 0 generation of the irradiated line WD14.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 60 Co γ-rays have also been used to construct mutant libraries in plants. For instance, 10 accessions of tetraploid wheat were irradiated with 60 Co γ-rays, which resulted in several novel mutation resources for wheat breeding [19]. The efficiency of different doses of 60 Co γ-rays was extensively investigated in tomato and potato (Solanum tuberosum L.) [10,20].…”
Section: Introductionmentioning
confidence: 99%